Phenologycal Leaves Senescense of Fabaceae during Dry Season in Purwodadi Botanic Garden (Case Study of Fabaceae Adaptation to Water Limitted) - Danarto, Setyawan Agung (Proceeding International Conference on Global Resource Conservation, 2013)
Fabaceae family has spread-distribution in the tropic region which much potency for human live in the world such as timber, medicine, food, etc. Phenology data give some information which has ecological value, such as character of species and climate change effect to plant activity. Study of leaves senescense of Fabaceae was conducted in Purwodadi Botanic Garden on July â October 2012. Materials of this researches are 79 selected species of Fabaceae. Estimation method of the abundance of leaves senescense was scored 0-4. Air temperature was observed periodically. The conclusions of this research are there four model of leaves senescense and adaptation of Fabaceae (full leaves senescense, leaves senescense and fruiting, evergreen, and less of leaves senescense). More information will be presented in this paper. Â Keywords: Fabaceae, dry season, leaves senescense Â  Â Â Â